The first expiriens of getting offspring of bester in Daghestan - A. O. Shaihulislamov; N. M. Gadzhimusayev; Ph. M. Magomayev; V. G. Chipinov; A. A. Korchunov (Юг России: экология, развитие)
The questions are examined in the article, connected with formation of the bloodstock of sturgeon fishes on the enterprises of aquaculture and obtaining their offspring. The technological schemes of work with the breeders of bester on the Shirokolskiy fishing industry are combined.